Escape Vectors, Gravitational Pulls, and Machine Ontology: Politics and Sense-making in Ryōsuke Takahashi’s "FLAG" - Reid, Eamon (Cinema: Journal of Philosophy and the Moving Image, 2024)
Japanese popular culture can be comprehended as an ideological battleground where political notions are postulated and speculated on, including popular mecha anime. This paper focuses on the mecha science fiction of Takahashi Ryōsuke to think the relation between anime media and sense-making. I critically analyse Takahashi’s FLAG. In the series, the photojournalist Saeko Shirasu is assigned to a special forces’ unit, SDC (or “seedac”) that is tasked by the United Nations Forces to reclaim a UN flag. This flag attained symbolic value following its being photographed by Shirasu, which depicts civilians raising the flag in the war-torn Uddiyana, plunged into civil war following the explosion of sectarian religious differences among Buddhists and a native belief system. The flag became a symbol for peace but was stolen by the extremist “Gelut Sect” to disrupt peace accords. I take sense-making to be connected to the democratic political problem of orientation as critically disucssed by Hannah Richter. This paper both attempts to grasp how Takahashi uses anime to think the relation between media and sense-making and uses Takahashi’s anime to conceptualize the relation between politics, media, and sense-making. I read FLAG from the perspective of MOO, arguing that various media machines–from cameras to informational fragments–have the capacity to interrupt sense. In this way, what I call the “journalist-assemblage” constitutes what Bryant terms a “rogue object”. Rogue objects constitute escape vectors that can be followed to depart from oppressive gravities. This is a political matter of orientation. I use Bryant’s typology of gravities to make this textual point in Takahashi explicit, but also to make the meta-textual argument that anime can be utilized to disrupt given sense-making practices. Adjacent to this, I make an argument contra Grant Hamilton for the relevance of the critical and philosophical interpretation of texts.